Analysis Risk Management Application e-Raport Using COBIT 4.1 - Deswinda Sari Hasibuan; Resad Setyadi (Soegijapranata Catholic University, 2022)
The role of information technology in increasing the use of e-Raport is to make it easier for schools to input student data. The e-Raport application is very important because it is a system to make it easier for teachers, staff, students, parents, and the Ministry of Education and Culture to find out the results of student learning analysis at SMK N 1 Balige as a means of communication between schools, students and parents of students. The problem with e-Report at SMK N 1 Balige is that there is an error when using the application to input data. The purpose of this study was to analyze risk management in the e-Raport application at SMK N 1 Balige. This research method uses quantitative methods. In measuring IT risk management, the author uses the Control Objective for Information and Related Technology (COBIT) 4.1 domain Plan and Organize (PO) framework, especially PO9 (Assessment and Manage IT risk). The result of this research is the value of the maturity level of the risk management application of e-Raport at SMK N 1 Balige is 2.6088. The maturity level of the e-Report of SMK N 1 Balige is Defined. Recommendations from this study are the need for a special person to control the e-Raport application at SMK N 1 Balige and training in the use of the e-Raport application.